Reducing brain TACE activity improves neuroinflammation and cardiac function in heart failure rats - Yu, Yang; Xue, Baojian; Irfan, Nafis Md; Beltz, Terry; Weiss, Robert M; Johnson, Alan Kim; Felder, Robert B; Wei, Shun-Guang (Frontiers in Physiology, 2022)
Tumor necrosis factor (TNF)-α converting enzyme (TACE) is a key metalloprotease mediating ectodomain shedding of a variety of inflammatory mediators, substrates, and growth factors. We previously reported that TACE-mediated production of TNF-α in the hypothalamic paraventricular nucleus (PVN) contributes to sympathetic excitation in heart failure (HF). Here, we sought to determine whether central interventions in TACE activity attenuate neuroinflammation and improve cardiac function in HF. Myocardial infarction-induced HF or sham-operated (Sham) rats were treated with bilateral PVN microinjection of a TACE siRNA or a 4-week intracerebroventricular (ICV) infusion of the TACE inhibitor TAPI-0. Compared with Sham rats, scrambled siRNA-treated HF rats had higher TACE levels in the PVN along with increased mRNA levels of TNF-α, TNF-α receptor 1 and cyclooxygenase-2. The protein levels of TNF-α in cerebrospinal fluid and phosphorylated (p-) NF-κB p65 and extracellular signal-regulated protein kinase (ERK)1/2 in the PVN were also elevated in HF rats treated with scrambled siRNA. The expression of these inflammatory mediators and signaling molecules in the PVN of HF rats were significantly attenuated by TACE siRNA. Interestingly, the mRNA level of TNF-α receptor 2 in the PVN was increased in HF treated with TACE siRNA. Moreover, sympathetic excitation, left ventricular end-diastolic pressure, pulmonary congestion, and cardiac hypertrophy and fibrosis were reduced by PVN microinjection of TACE siRNA. A 4-week treatment with ICV TAPI-0 had similar effects to ameliorate these variables in HF rats. These data indicate that interventions suppressing TACE activity in the brain mitigate neuroinflammation, sympathetic activation and cardiac dysfunction in HF rats.